Preparation method of superfine ES fiber
By using the melt mixing of polyethylene and modified antibacterial agent in ES fibers and high-voltage electrostatic assisted melt spinning technology, combined with multiple drafting and relaxation heat setting, the problems of insufficient antibacterial and hygroscopicity of existing ES fibers are solved, and ultrafine ES fibers with high strength, good hygroscopicity and antibacterial properties are produced.
Patent Information
- Application Number
- CN202411464164.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-11
AI Technical Summary
The existing ES fibers are not antibacterial, cannot absorb moisture quickly, and their products are easily damaged, which cannot meet the production requirements in different fields.
Polyethylene and modified antibacterial agent are melted and mixed into the cortex and polydiethanol terephthalate as the core layer. Through high-voltage electrostatic assisted melt spinneret, multiple drafting and relaxation heat setting are performed to produce ultrafine ES fibers.
It improves the tensile fracture strength, hygroscopicity and antibacterial properties of the fiber, and meets the needs of high strength, good hygroscopicity and antibacteriality.
Smart Images

Figure BDA0005092799930000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ES fibers, in particular to a method for preparing ultrafine ES fibers. Background Art
[0002] ES fiber is a polyolefin fiber developed by Japan's JNC Corporation, which has won the Japan Fiber Society Technology Achievement Award. As a new type of thermal bonding composite fiber, ES fiber has received high praise in the world. The hot air non-woven fabric made of ES fiber as a raw material has the characteristics of softness, low temperature processing, non-toxicity, non-irritation and light weight. It is an ideal material for manufacturing disposable sanitary products such as sanitary napkins, infant diapers, and adult diapers.
[0003] In recent years, with the increase in the market size of disposable sanitary products, and the high-end development of terminal maternal and child products and feminine hygiene products, hot air nonwovens have gradually replaced spunbond nonwovens to become the ideal material for the new generation of disposable sanitary products, which will also have a significant driving force on the market demand for ES fibers. However, most ES fibers on the market have weak antibacterial properties, cannot absorb moisture quickly, and the manufactured products can be easily destroyed, which cannot meet the production requirements of different fields. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing ultrafine ES fibers to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing ultrafine ES fibers, comprising the following preparation steps:
[0006] (1) Dissolve 2 to 8 parts of silver nitrate and 5 to 15 parts of S-acetyl-L-glutathione in 98 to 296 parts of deionized water, adjust the pH to 6 to 7 with an aqueous sodium hydroxide solution, heat to 70 to 90° C., stir at 120 rpm for 1 to 2 hours, filter the filtrate, let stand at 20 to 30° C. for 36 to 60 hours, filter the solid, and dry at 50 to 60° C. for 4 to 8 hours to obtain a modified antibacterial agent;
[0007] (2) 84-96 parts of polyethylene with a melting point of 105-110°C, 7-10 parts of a modified antibacterial agent, and 2-4 parts of nano-silicon dioxide with a particle size of 15 nm are mixed uniformly, and the mixture is extruded and sliced. The head temperature is 120-150°C, the screw speed is 180-220 r / min, the extrusion pressure is 7-11 MPa, and the shear rate is 130-210 s -1 , get the raw material of cortex;
[0008] (3) pre-crystallizing and drying the core layer raw material and the skin layer raw material at 120-140° C. and 90-100° C., respectively, melting at different temperatures, spraying out in a filament shape with the assistance of high-voltage static electricity, and cooling to obtain ultrafine composite monofilaments;
[0009] (4) The ultra-fine composite monofilament is oiled by an oil roller with an oil agent and wound into a 24F bundle;
[0010] (5) placing the bundled wire between the first drawing machine and the second drawing machine for one drawing, drawing it to 1.8 to 2.0 times; wherein the temperature of the two drawing machines is 55 to 75° C., the winding speed of the first drawing machine is 1400 to 1600 m / min, and the winding speed of the second drawing machine is 1100 to 1500 m / min;
[0011] (6) placing the bundled wire between the second drawing machine and the third drawing machine for secondary drawing, drawing it to 3.0 to 3.5 times; wherein the temperature of the third drawing machine is 70 to 90° C., and the winding speed is 1200 to 1600 m / min;
[0012] (7) The drawn filament bundle is curled at 70-80°C, relaxed and heat-set at 100-110°C, and cut to obtain ultrafine ES fibers.
[0013] Furthermore, the concentration of the sodium hydroxide aqueous solution in step (1) is 0.5 mol / L.
[0014] Furthermore, the core layer material in step (3) is polyethylene terephthalate chips with a melting point of 250°C.
[0015] Furthermore, in step (3), the volume ratio of the core layer raw material to the skin layer raw material is 1:2.5-2.7.
[0016] Furthermore, the different temperatures in step (3) are 275-285°C for the core layer spinning screw and 120-150°C for the skin layer spinning screw.
[0017] Furthermore, the voltage of the high-voltage static electricity in step (3) is 50 to 80 kV.
[0018] Furthermore, the cooling in step (3) is performed at a cooling air temperature of 18 to 22° C., a wind speed of 0.6 to 1.4 m / s, a wind pressure of 600 to 800 Pa, and a cooling time of 30 to 60 min.
[0019] Furthermore, the oil agent in step (4) is an antistatic oil agent with a concentration of 1.0%wt.
[0020] Furthermore, in step (4), the rotation direction of the oil roller is opposite to the fiber direction, and the size of the oil roller is The rotation speed is 20-30r / min, and the distance between the oil roller and the spinneret is 4.5m.
[0021] Furthermore, the ultrafine ES fiber is 0.5 dtex.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] The invention uses polyethylene and a modified antibacterial agent melt-mixed as a skin layer and polyethylene terephthalate as a core layer. First, high-voltage electrostatic assisted melt spinning is used to make the polymer melt jet uniformly refined, thereby improving the tensile fracture strength, while increasing the porosity, improving the electrostatic adsorption effect of the fiber, and enhancing the hydrophilicity, thereby achieving a good hygroscopic effect; then, a primary stretching is performed by utilizing the difference in the front and rear stretching speeds of a first stretching machine and a second stretching machine to further thin the fiber, so that the grains in the fiber are arranged in order and the mechanical strength is improved; then, a secondary stretching is performed in a steam box by a second stretching machine and a third stretching machine to assist the primary stretching, so that the macromolecules are further oriented and crystallized, the heat shrinkage phenomenon during production is reduced, and the mechanical strength and air permeability are indirectly improved; finally, the ultrafine ES fiber is relaxed, dried, and cut to achieve the effects of high strength, good hygroscopicity, and antibacterial.
[0024] Among them, the modified antibacterial agent is made of S-acetyl-L-glutathione and silver nitrate; the carboxyl group in S-acetyl-L-glutathione is used to coordinate with silver nitrate to form a network structure with silver as the central ion, thereby achieving a slow controlled release of silver ions, significantly improving the overall thermal stability and antibacterial properties, and introducing sulfur elements, which can react with enzymes in bacteria, destroy the cell walls of bacteria, make the bacteria lose their ability to survive, and achieve antibacterial effects. At the same time, the network structure has a relatively high porosity, and melt mixing with polyethylene can enhance the overall moisture absorption effect and initially improve the hygroscopicity. On this basis, the molecular chain contains hydrophilic amino groups, which further enhance the hygroscopicity of the fiber. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the ultrafine ES fibers prepared in the following examples.
[0027] Breaking strength: The same weight of the embodiment and the comparative example were tested according to GB / T 14337.
[0028] Wicking height: Take the same weight of the embodiment and the comparative example, and make the same specification of ES composite fiber non-woven fabric (weight 400g / m 2 ) fabric, use a capillary tester to test the wicking height of the fiber.
[0029] Escherichia coli inhibition rate and Staphylococcus aureus inhibition rate: Take the same weight of the embodiment and the comparative example, and make ES composite fiber non-woven fabrics (weight 400g / m 2 ) fabrics, tested according to GB / T20944.3.
[0030] Fungal inhibition rate: The same weight of the embodiment and the comparative example were made into ES composite fiber non-woven fabrics (weight 400g / m 2 ) fabrics, tested according to GB / T 20944.2.
[0031] Example 1: (1) 2 parts of silver nitrate and 5 parts of S-acetyl-L-glutathione were dissolved in 98 parts of deionized water, the pH was adjusted to 6 with a 0.5 mol / L sodium hydroxide aqueous solution, the temperature was raised to 70°C, stirred at 120 rpm for 1 hour, the filtrate was filtered, and the mixture was allowed to stand at 20°C for 36 hours. The solid was filtered and dried at 50°C for 4 hours to obtain a modified antibacterial agent;
[0032] (2) 84 parts of polyethylene with a melting point of 105°C, 7 parts of a modified antibacterial agent, and 2 parts of nano-silicon dioxide with a particle size of 15 nm were mixed evenly, and then extruded and sliced. The head temperature was 120°C, the screw speed was 180 r / min, the extrusion pressure was 7 MPa, and the shear rate was 130 s -1 , get the raw material of cortex;
[0033] (3) Pre-crystallizing and drying polyethylene terephthalate chips and skin layer raw materials with a melting point of 250° C. at 120° C. and 90° C., respectively, melting the chips at a core spinning screw temperature of 275° C. and a skin spinning screw temperature of 120° C., spraying the chips in a filamentous form with the assistance of 50 kV high-voltage static electricity, and cooling the chips for 30 minutes at a cooling air temperature of 18° C., a wind speed of 0.6 m / s, and a wind pressure of 600 Pa to obtain ultrafine composite monofilaments; the volume ratio of the polyethylene terephthalate chips to the skin layer raw materials is 1:2.5;
[0034] (4) The ultrafine composite monofilament is oiled by an oil roller with an antistatic oil agent having a concentration of 1.0% wt and wound into a 24F bundle; wherein the rotation direction of the oil roller is opposite to the fiber direction, and the size of the oil roller is The speed is 20r / min, and the distance between the oil roller and the spinneret is 4.5m;
[0035] (5) placing the bundled wire between the first drawing machine and the second drawing machine for one drawing, and drawing it to 1.8 times; wherein the temperature of the two drawing machines is 55° C., the winding speed of the first drawing machine is 1400 m / min, and the winding speed of the second drawing machine is 1100 m / min;
[0036] (6) The bundled wire is then placed between the second drawing machine and the third drawing machine for secondary drawing, and the drawing is extended to 3.0 times; wherein the temperature of the third drawing machine is 70°C and the winding speed is 1200m / min;
[0037] (7) The stretched filaments are curled at 70°C, relaxed and heat-set at 100°C, and cut to obtain ultrafine ES fibers of 0.5 dtex.
[0038] Example 2: (1) 5 parts of silver nitrate and 10 parts of S-acetyl-L-glutathione were dissolved in 197 parts of deionized water, the pH was adjusted to 6.5 with a 0.5 mol / L sodium hydroxide aqueous solution, the temperature was raised to 80°C, stirred at 120 rpm for 1.5 h, the filtrate was filtered, and the mixture was allowed to stand at 25°C for 48 h. The solid was filtered and dried at 55°C for 6 h to obtain a modified antibacterial agent;
[0039] (2) 90 parts of polyethylene with a melting point of 107.5°C, 8.5 parts of a modified antibacterial agent, and 3 parts of nano-silicon dioxide with a particle size of 15 nm were mixed evenly, and the mixture was extruded and sliced. The head temperature was 135°C, the screw speed was 200 r / min, the extrusion pressure was 9 MPa, and the shear rate was 170 s -1 , obtain the core layer raw material;
[0040] (3) Pre-crystallizing and drying polyethylene terephthalate chips and skin layer raw materials with a melting point of 250° C. at 130° C. and 95° C., respectively, melting the chips at a core spinning screw temperature of 280° C. and a skin spinning screw temperature of 135° C., spraying the chips in a filamentous form with the assistance of 65 kV high-voltage static electricity, and cooling the chips for 45 minutes at a cooling air temperature of 20° C., a wind speed of 1.0 m / s, and a wind pressure of 700 Pa to obtain ultrafine composite monofilaments; the volume ratio of the polyethylene terephthalate chips to the skin layer raw materials is 1:2.6;
[0041] (4) The ultrafine composite monofilament is oiled by an oil roller with an antistatic oil agent having a concentration of 1.0% wt and wound into a 24F bundle; wherein the rotation direction of the oil roller is opposite to the fiber direction, and the size of the oil roller is The speed is 25r / min, and the distance between the oil roller and the spinneret is 4.5m;
[0042] (5) placing the bundled wire between the first drawing machine and the second drawing machine for one drawing, and drawing it to 1.9 times; wherein the temperature of the two drawing machines is 65° C., the winding speed of the first drawing machine is 1500 m / min, and the winding speed of the second drawing machine is 1300 m / min;
[0043] (6) The bundled wire is then placed between the second drawing machine and the third drawing machine for secondary drawing, and the drawing is extended to 3.25 times; wherein the temperature of the third drawing machine is 80°C and the winding speed is 1400m / min;
[0044] (7) The stretched filaments were curled at 75°C, relaxed and heat-set at 105°C, and cut to obtain ultrafine ES fibers of 0.5 dtex.
[0045] Example 3: (1) 8 parts of silver nitrate and 15 parts of S-acetyl-L-glutathione were dissolved in 296 parts of deionized water, the pH was adjusted to 7 with a 0.5 mol / L sodium hydroxide aqueous solution, the temperature was raised to 90°C, stirred at 120 rpm for 2 h, the filtrate was filtered, and the mixture was allowed to stand at 30°C for 60 h. The solid was filtered and dried at 60°C for 8 h to obtain a modified antibacterial agent;
[0046] (2) 96 parts of polyethylene with a melting point of 110°C, 10 parts of a modified antibacterial agent, and 4 parts of nano-silicon dioxide with a particle size of 15 nm were mixed evenly, and then extruded and sliced. The head temperature was 150°C, the screw speed was 220 r / min, the extrusion pressure was 11 MPa, and the shear rate was 210 s -1 , get the raw material of cortex;
[0047] (3) Pre-crystallizing and drying polyethylene terephthalate chips and skin layer raw materials with a melting point of 250° C. at 140° C. and 110° C., respectively, melting the chips at a core spinning screw temperature of 285° C. and a skin spinning screw temperature of 150° C., spraying the chips in a filamentous form with the assistance of 80 kV high-voltage static electricity, and cooling the chips for 60 min at a cooling air temperature of 22° C., a wind speed of 1.4 m / s, and a wind pressure of 800 Pa to obtain ultrafine composite monofilaments; the volume ratio of the polyethylene terephthalate chips to the skin layer raw materials is 1:2.7;
[0048] (4) The ultrafine composite monofilament is oiled by an oil roller with an antistatic oil agent having a concentration of 1.0% wt and wound into a 24F bundle; wherein the rotation direction of the oil roller is opposite to the fiber direction, and the size of the oil roller is The speed is 30r / min, and the distance between the oil roller and the spinneret is 4.5m;
[0049] (5) placing the bundled wire between the first drawing machine and the second drawing machine for one drawing, and drawing it to 2.0 times; wherein the temperature of the two drawing machines is 75° C., the winding speed of the first drawing machine is 1600 m / min, and the winding speed of the second drawing machine is 1500 m / min;
[0050] (6) The bundled wire is then placed between the second drawing machine and the third drawing machine for secondary drawing, and the drawing is extended to 3.5 times; wherein the temperature of the third drawing machine is 90°C and the winding speed is 1600m / min;
[0051] (7) The stretched filaments were curled at 80°C, relaxed and heat-set at 110°C, and cut to obtain ultrafine ES fibers of 0.5 dtex.
[0052] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is the difference in step (3), which is changed to: pre-crystallize and dry the polyethylene terephthalate slices and the skin layer raw material at 130°C and 95°C respectively, melt them at a core layer spinning screw temperature of 280°C and a skin layer spinning screw temperature of 135°C, spray them in a filamentous state, and cool them for 45 minutes at a cooling air temperature of 20°C, a wind speed of 1.0 m / s, and a wind pressure of 700 Pa to obtain an ultrafine composite monofilament; the volume ratio of the polyethylene terephthalate slices to the skin layer raw material is 1:2.6. The remaining steps are the same as those in Example 2.
[0053] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is step (6). The remaining steps are the same as Example 2.
[0054] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that there is no step (1), and step (2) is changed to: 90 parts of polyethylene with a melting point of 107.5°C, 8.5 parts of silver nitrate, and 3 parts of nano-silicon dioxide with a particle size of 15 nm are mixed uniformly, and the mixed and extruded slices are cut into pieces. The head temperature is 135°C, the screw speed is 200r / min, the extrusion pressure is 9MPa, and the shear rate is 170s- 1 The remaining steps are the same as those in Example 2.
[0055] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is omitted, and step (2) is changed to: 90 parts of polyethylene with a melting point of 107.5°C, 8.5 parts of S-acetyl-L-glutathione, and 3 parts of nano-silicon dioxide are mixed uniformly, and the mixed and extruded slices are sliced. The head temperature is 135°C, the screw speed is 200r / min, the extrusion pressure is 9MPa, and the shear rate is 170s- 1 The remaining steps are the same as those in Example 2.
[0056] Effect example
[0057] Table 1 below shows the performance analysis results of the ultrafine ES fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0058] Table 1
[0059]
[0060] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that by high-voltage electrostatic assisted melt spinning, the polymer melt jet is uniformly refined, the tensile strength is improved, and the porosity is increased, the electrostatic adsorption effect of the fiber is improved, and the hydrophilicity is enhanced, thereby achieving a good hygroscopic effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the secondary drawing can assist the primary drawing, so that the macromolecules are further oriented and crystallized, the heat shrinkage phenomenon during production is reduced, and the mechanical strength and air permeability are indirectly improved; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the secondary drawing can assist the primary drawing, so that the macromolecules are further oriented and crystallized, the heat shrinkage phenomenon during production is reduced, and the mechanical strength and air permeability are indirectly improved; 3, it can be found that the use of S-acetyl-L-glutathione can form a network structure with a relatively high void, and the introduction of amino groups can significantly improve the overall thermal stability and hygroscopic effect, and the introduction of sulfur elements can react with enzymes in bacteria to destroy the cell walls of bacteria, causing the bacteria to lose their ability to survive, thereby achieving an antibacterial effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that silver ions are successfully introduced through silver nitrate, and coordinated to form a structure with silver as the central ion, thereby achieving the effect of slowly controlled release of silver ions and significantly improving the antibacterial performance.
[0061] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing ultrafine ES fibers, characterized in that: The method comprises the following preparation steps: (1) Dissolve 2 to 8 parts of silver nitrate and 5 to 15 parts of S-acetyl-L-glutathione in 98 to 296 parts of deionized water, adjust the pH to 6 to 7 with an aqueous sodium hydroxide solution, heat to 70 to 90° C., stir at 120 rpm for 1 to 2 hours, filter the filtrate, let stand at 20 to 30° C. for 36 to 60 hours, filter the solid, and dry at 50 to 60° C. for 4 to 8 hours to obtain a modified antibacterial agent; (2) 84-96 parts of polyethylene with a melting point of 105-110°C, 7-10 parts of a modified antibacterial agent, and 2-4 parts of nano-silicon dioxide with a particle size of 15 nm are mixed uniformly, and the mixture is extruded and sliced. The head temperature is 120-150°C, the screw speed is 180-220 r / min, the extrusion pressure is 7-11 MPa, and the shear rate is 130-210 s -1 , get the raw material of cortex; (3) pre-crystallizing and drying the core layer raw material and the skin layer raw material at 120-140° C. and 90-100° C., respectively, melting at different temperatures, spraying out in a filament shape with the assistance of high-voltage static electricity, and cooling to obtain ultrafine composite monofilaments; (4) The ultra-fine composite monofilament is oiled by an oil roller with an oil agent and wound into a 24F bundle; (5) placing the bundled wire between the first drawing machine and the second drawing machine for one drawing, drawing it to 1.8 to 2.0 times; wherein the temperature of the two drawing machines is 55 to 75° C., the winding speed of the first drawing machine is 1400 to 1600 m / min, and the winding speed of the second drawing machine is 1100 to 1500 m / min; (6) placing the bundled wire between the second drawing machine and the third drawing machine for secondary drawing, drawing it to 3.0 to 3.5 times; wherein the temperature of the third drawing machine is 70 to 90° C., and the winding speed is 1200 to 1600 m / min; (7) The drawn filament bundle is curled at 70-80°C, relaxed and heat-set at 100-110°C, and cut to obtain ultrafine ES fibers.
2. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution in step (1) is 0.5 mol / L.
3. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The core layer raw material of step (3) is polyethylene terephthalate chips with a melting point of 250°C.
4. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: In step (3), the volume ratio of the core layer raw material to the skin layer raw material is 1:2.5-2.
7.
5. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The different temperatures in step (3) are 275-285°C for the core layer spinning screw and 120-150°C for the skin layer spinning screw.
6. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The voltage of the high-voltage static electricity in step (3) is 50 to 80 kV.
7. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The cooling in step (3) is performed at a cooling air temperature of 18 to 22° C., a wind speed of 0.6 to 1.4 m / s, a wind pressure of 600 to 800 Pa, and a cooling time of 30 to 60 min.
8. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The oil agent in step (4) is an antistatic oil agent with a concentration of 1.0%wt.
9. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The rotation direction of the oil roller in step (4) is opposite to the fiber direction, the size of the oil roller is φ250×230mm, the rotation speed is 20-30r / min, and the distance between the oil roller and the spinneret is 4.5m.
10. The method for preparing ultrafine ES fiber according to claim 1, characterized in that: The ultrafine ES fiber has a thickness of 0.5 dtex.